2019
DOI: 10.3390/molecules24142589
|View full text |Cite
|
Sign up to set email alerts
|

Great Enhancement of Carbon Energy Storage through Narrow Pores and Hydrogen-Containing Functional Groups for Aqueous Zn-Ion Hybrid Supercapacitor

Abstract: The proton transfer mechanism on the carbon cathode surface has been considered as an effective way to boost the electrochemical performance of Zn-ion hybrid supercapacitors (SCs) with both ionic liquid and organic electrolytes. However, cheaper, potentially safer, and more environmental friendly supercapacitor can be achieved by using aqueous electrolyte. Herein, we introduce the proton transfer mechanism into a Zn-ion hybrid supercapacitor with the ZnSO4 aqueous electrolyte and functionalized activated carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…At this time, more active materials inside the electrode have no time to participate in the redox reaction, so the surface capacitive contribution process is over 50%, which is consistent with many previously reported studies. 54,55 Additionally, the capacitance contribution percentage of the diffusion-controlled process gradually decreases with increasing scan rate. This result indicates that the surfacecontrolled process occupies a dominant part of charge storage at every scan rate, which is beneficial to the integrity, rate performance, and long cycling stability of the electrode nanostructure.…”
Section: Resultsmentioning
confidence: 99%
“…At this time, more active materials inside the electrode have no time to participate in the redox reaction, so the surface capacitive contribution process is over 50%, which is consistent with many previously reported studies. 54,55 Additionally, the capacitance contribution percentage of the diffusion-controlled process gradually decreases with increasing scan rate. This result indicates that the surfacecontrolled process occupies a dominant part of charge storage at every scan rate, which is beneficial to the integrity, rate performance, and long cycling stability of the electrode nanostructure.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al revealed both experimentally and theoretically an enhanced performance by controlling the hydrogen-containing functional groups (−OH and −NH functions) of the activated carbon materials. The characterization results revealed the hydrogen-containing functional groups are the key factor on the electrochemical property SCs with aqueous electrolytes . On the other hand, the Raman spectra for the CF and the acid-treated CF electrodes were examined, as shown in Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the electrolyte concentration and the test accuracy of the electrochemical workstation will also have impacts, and these problems also exist in the previously reported literature. 64 This novel electrode possesses the following advantages: An ASC device is assembled by pairing the C-NiCo 2 O 4 /C@ Ni−Co−S positive electrode with the AC negative electrode to test the practical application potential of electrode materials. Before the ASC device is assembled, the performance of the activated carbon electrode is tested in the three-electrode test system, as shown in Figure S8.…”
Section: Methodsmentioning
confidence: 99%